Infectious bloody diarrhea in children 2 month – 5years, Descriptive hospital Based Study - Al-Beldawi, Dhia H.; Al-Ma'eeni, Afrah A.; Ahmed, Mustafa Sh. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Dysentery is an important cause of morbidity and mortality associated with diarrhea. About 10% of all diarrheal episodes in children less than 5 years are dysenteric, but these cause about 15% of all deaths attributed to diarrhea.Objective : To demonstrate the most common pathogens causing bloody diarrhea in children between 2 months and 5 years old, to describe some of the associated factors accompanying bloody diarrhea and to highlight the most important clinical features.Patients and methods: A descriptive study of 82 children, between the age of 2 months to 5 years with bloody diarrhea, who were admitted to the Children Welfare Teaching Hospital/ Medical City/Baghdad during the period between 1st of March 2009 to 28th of February 2010. Information regarding demographic data was taken from their parents. All the patients were examined carefully mainly for the signs and degree of dehydration. General stool examination and stool culture done for patients with bloody diarrhea. Other 100 patients with acute watery diarrhea were also taken as a comparison group.Results: Entamoeba histolytica trophozoite was the most common isolated pathogen in the study group specimens. It was identified in 38 (46.3%) of patients followed by Shigella species in 10 (12.2%) cases and the least was non typhoidal salmonella in 5 (6.1%) cases. The most vulnerable age was 2-24 months 51(62.2%) cases. Fifty eight and half percent of patients were from urban areas. Half of the patients (50%) were bottle fed. The majority had chlorinated tap water supply (82.9%). This study showed a higher frequency of the following symptoms: Fever (73.2%), Tenesmus (46.3%), Rectal prolapse (1.2%) and convulsion (4.9%) in patients with bloody diarrhea; while in patients with watery diarrhea, the frequencies of these symptoms were: (62%, 28%, 0% and 1% respectively), Severe dehydration was observed in only (15.9%) of cases and the majority of them were seen in patients with bacterial bloody diarrhea. Conclusions: Entamoeba histolytica was the most frequent offending pathogen in patients with bloody diarrhea in this study. Infants 2-24 months old were the main affected group. Bottle feeding preference, and non-boiling of drinking water made children more prone to have bloody diarrhea. High fever and tenesmus were the most frequent clinical symptoms associated with bloody diarrhea. More frequent bowel motions, high fever, and convulsion were all more commonly seen with bacterial bloody diarrhea than in amebic bloody diarrhea.